1996
DOI: 10.1111/j.2042-7158.1996.tb05917.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plasma-protein Binding on Analgesic Effect of Methadone in Rats with Spontaneous Withdrawal

Abstract: The effect of spontaneous withdrawal on alpha 1-acid glycoprotein (AAG) levels and methadone protein binding has been studied in the rat. Animals were made physically dependent on morphine by providing morphine HCl in drinking water for three weeks. The natural opiate withdrawal was induced in rats by substituting the morphine solution with drinking water. The severity of the abstinence syndrome was assessed at various time intervals. After 12 h of withdrawal, the animals showing abstinence signs and low morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Thus, heroin addicts who show objective signs of opiate withdrawal tend to have elevated plasma levels of α 1 ‐acid glycoprotein and increased ex vivo plasma binding of methadone compared with normal subjects [ 44]. Similarly, increased plasma binding of methadone has been observed in rats with withdrawal effects immediately after chronic heroin administration [ 45]. Hence, it may be postulated that substitution of heroin with methadone and suppression of opiate withdrawal symptoms is accompanied by a decrease in the level of α 1 ‐acid glycoprotein and of methadone binding.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, heroin addicts who show objective signs of opiate withdrawal tend to have elevated plasma levels of α 1 ‐acid glycoprotein and increased ex vivo plasma binding of methadone compared with normal subjects [ 44]. Similarly, increased plasma binding of methadone has been observed in rats with withdrawal effects immediately after chronic heroin administration [ 45]. Hence, it may be postulated that substitution of heroin with methadone and suppression of opiate withdrawal symptoms is accompanied by a decrease in the level of α 1 ‐acid glycoprotein and of methadone binding.…”
Section: Discussionmentioning
confidence: 99%
“…A study in opiate-tolerant rats [41] has shown that enforced abstinence is associated with an increase in a 1 -acid glycoprotein, a major binding site for methadone in plasma [39]. Furthermore, opiate users about to begin a programme of methadone treatment are reported to have elevated plasma concentrations of this protein (1.22±0.10 s.d.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…(16) reported that the signs of spontaneous morphine withdrawal consisted of teeth‐chattering, mastication, wet‐dog shakes, yawning, forepaw tremors, ptosis, eye twitching, piloerection and diarrhoea. Withdrawal lasted for 84 h, with the most severe manifestation of signs occurring at 36 h. In a similar study, adult rats became physically dependent within 3 weeks on morphine added to their drinking water (17). Withdrawal throughout a 72‐h period consisted of posturing, vocalization on touch, ptosis, diarrhoea, rearing, jumping, wet‐dog shakes and teeth chattering, with the most severe manifestation of signs occurring at 24 h. Therefore, in both infant and adult rats spontaneous morphine withdrawal lasts for approximately 72 h, with the most severe manifestation of signs occurring from 24 to 48 h.…”
Section: Comparison Of Spontaneous Morphine Withdrawal Between Infantmentioning
confidence: 97%